Gene Expression and Cellular Markers of Occupational Radiation Exposure in Chernobyl Shelter Construction Workers. Issue 1 (July 2020) - Bazyka, Dimitry; Ilienko, Iryna; Golyarnik, Natalya; Belyaev, Oleg; Lyaskivska, Olena
Abstract : Abstract: Low-dose radiation effects were studied in Ukrainian personnel of the Chernobyl exclusion zone. The aim of this study was to determine the influence of borderline exposure to annual professional limits and age on expression of molecular markers. Study groups included 300 radiation workers performing construction work on the New Safe Confinement (Arch) upon the Chernobyl "Shelter" [external dose, 26.1 ± 18.1 mSv; age, 43.1 ± 10.3 y overall and 48.7 ± 5.9 y for 69 control persons]. Methods included gene expression using RT-PCR, flow cytometry of lymphocyte antigens, gamma-H2AX, Cyclin D1 expression, and relative telomere length using flow-FISH. A statistically significant upregulation of VEGFA BAX, DDB2, NFKB1 was shown at doses below 35 mSv. In workers aged under 40 y with doses higher than 35 mSv, an upregulation of 16 genes was revealed— VEGFA, TERF2, TERF1, BIRC5, BAX, TP53, DDB2, CDKN1B, CDKN2A, NFKB2, MAPK14, TGFBR1, MKNK2, CDKN1A, NFKB1, TP53I3; and four genes were downregulated— MADD, FASL, CSF2, and TERT. In workers older than 40 y, 8 genes were upregulated and 12 were downregulated. All groups showed an increased and dose-dependent gamma-H2AX expression. Downregulation of CCND 1 genes in older groups was accompanied by lower numbers of Cyclin D1 protein expression and lower CD3 + and CD4 + cell counts. Upregulation of CSF2 in those over 40 y old positively correlated with B-cell and NK-cell counts. A non-linear type of gene expression response was demonstrated: in doses over 35 mSv for those over 40 y, the increased expression of gamma-H2AX is associated with upregulation of cell survival positive regulators— BIRC5, BRCA1, DDB2, CCND1, TERT genes, and longer telomeres; the younger age group was characterized by TERF1 and TERF2 upregulation and telomere shortening.